2020
DOI: 10.1183/13993003.02162-2020
|View full text |Cite
|
Sign up to set email alerts
|

LAM is another small airway disease: lessons from microCT

Abstract: ]. How do we take advantage and translate these new findings for treating patients? Given these new insights, we may decide to treat LAM patients based on the presence of small airway disease, as early as possible. Diagnostic issues will be potentially solved by the wider use of high-resolution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…17 The introduction of microcomputed tomography (microCT) has enabled three-dimensional (3D) morphologic assessments of lung tissues that are very difficult to achieve with conventional histologic analysis. 12,13,18,19 In addition, microCT of frozen air-inflated tissue enables quantitative assessment without shrinkage and physical cutting of tissues. 20 Mai et al 16 combined CT, microCT, and histologic assessment, and found that fibrosis and honeycomb cyst formation in IPF extend from the peripheral to the central region of the pulmonary lobules.…”
mentioning
confidence: 99%
“…17 The introduction of microcomputed tomography (microCT) has enabled three-dimensional (3D) morphologic assessments of lung tissues that are very difficult to achieve with conventional histologic analysis. 12,13,18,19 In addition, microCT of frozen air-inflated tissue enables quantitative assessment without shrinkage and physical cutting of tissues. 20 Mai et al 16 combined CT, microCT, and histologic assessment, and found that fibrosis and honeycomb cyst formation in IPF extend from the peripheral to the central region of the pulmonary lobules.…”
mentioning
confidence: 99%
“…Given the above evidence, it is clear that microCT can serve as a complementary, and in the future perhaps even an indispensable tool for routine pathology ( 32 ). Although significant technical advances have been made, there is still some work to be done.…”
Section: Discussionmentioning
confidence: 99%